Travel‐Related Chronic Hemorrhagic Leg Ulcer Infection by Shewanella algae. Issue 4 (22nd May 2013) - Wagner, Nicola; Otto, Lisa; Podda, Maurizio; Schmitt, York; Tappe, Dennis
Abstract : Shewanella algae is an emerging seawater‐associated bacterium. In immunocompromised patients, infections may result in bacteremia, osteomyelitis, and necrotizing fasciitis. Our patient, suffering from autoimmune vasculitis and myasthenia gravis, developed typical hemorrhagic bullae and leg ulcers because of S algae . She was treated efficiently with a combination of ciprofloxacin and piperacillin.